ANALISIS RASIO KEUANGAN PADA BANK BUMN dan BANK SWASTA GO PUBLIC TAHUN 2017-2019 - Dinda Palupy; Suwigyo Widagdo; Lia Rachmawati (Universitas Muhammadiyah Jember, 2022)
Abstract : This study aims to analyze the financial performance of state-owned banks and private banks in terms of financial ratio analysis. In addition, this study is also intended to analyze the differences financial performance between state-owned banks and private banks. This research was conducted from 2017 to 2019 which included 20 samples of banking companies consisting of 4 state-owned banks and 16 private banks which were taken using a purposive sampling technique. Data were analyzed using financial ratios consisting of LDR ratio, ROA ratio, ROE ratio, and CAR ratio. Then the data were analyzed using the Independent T-test method. The analytical tools used in this research are Microsoft Excel 2016 and SPSS Version 24. The results of the study based on financial ratio analysis show that state-owned banks have better financial performance than private banks. Then the results of the Independent T-test statistical test showed that there was no difference in financial performance in terms of LDR, ROA, and CAR ratios, only the ROE ratio showed significant differences in financial performance between state-owned banks and private banks. Keywords: Financial Performance, LDR, ROA, ROE, CAR, State-Owned Banks, Private Banks